Sálavé systémy vytápění. - Fouček, Petr (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Cílem bakalářské práce na téma „Sálavé systémy vytápění” je shrnout používané systémy, jejich jednotlivé komponenty, posoudit přednosti a nedostatky tohoto systému. Práce je zaměřená na všeobecné seznámení s vytápěním sálavým a přiblížení problematiky podlahového vytápění a vytápění průmyslových budov, jejich rozdělení a seznámení s jednotlivými principy.

The aim of my work on the theme„Radiant systems heating” is to summarize used systems, it’ s individual components, pass judgment on preferences and shortcomings of this systems. The work is oriented on general familiarization with radiant heating and approximation the proposition floor heating and rating industrial buildings, thein parting and identification with thein particular principle.
Radiant heating systems.
Keywords: Sálavé systémy; podlahové vytápění; sálavé panely; zářiče.; Radiant systems; floor heating; radiant panel; holder.